CSR Contribution to Socio-Economic Development: Evidence from Indonesian Islamic Banks - Aishath Muneeza; Aminudin Ma'ruf; Shahbaz Alam (Universitas Ahmad Dahlan, 2020)
Islamic banks play a significant role in social and environmental responsibility. It is known that Islamic finance is not merely profit-oriented but also looking at the prosperity of the society, as an ethical financial system Islamic finance give a massive contribution towards social responsibility. This exploratory study examines the relations between corporate social responsibility (CSR) practices of Indonesian Islamic banks and socio-economic development. The evidence presented is based on the published annual reports of 13 Islamic commercial banks in 2017. The findings of this research suggests that CSR is a priority of Indonesian Islamic banks and has correlation to the socio-economic development. Furthermore, the findings suggest that the robust guiding principles on CSR need to be developed and it has potential of Islamic banks credibility and profitability.